Dissecting the functional anatomy of auditory word repetition - Hope, Thomas M. H.; Prejawa, Susan; Parker Jones, ‘Ōiwi; Oberhuber, Marion; Seghier, Mohamed L.; Green, David W.; Price, Cathy J. (Frontiers in Human Neuroscience, 2014)
Auditory word repetition involves many different brain regions, whose functions are still far from fully understood. Here, we use a single, multi-factorial, within-subjects fMRI design to identify those regions, and to functionally distinguish the multiple linguistic and non-linguistic processing areas that are all involved in repeating back heard words. The study compared: (1) auditory to visual inputs; (2) phonological to non-phonological inputs; (3) semantic to non-semantic inputs; and (4) speech production to finger-press responses. The stimuli included words (semantic and phonological inputs), pseudowords (phonological input), pictures and sounds of animals or objects (semantic input), and coloured patterns and hums (non-semantic and non-phonological). The speech production tasks involved auditory repetition, reading and naming while the finger press tasks involved one-back matching. The results from the main effects and interactions were compared to predictions from a previously reported functional anatomical model of language based on a meta-analysis of many different neuroimaging experiments. Although many findings from the current experiment replicated those predicted, our within-subject design also revealed novel results by providing sufficient anatomical precision to distinguish several different regions within: (1) the anterior insula (a dorsal region involved in both covert and overt speech production, and a more ventral region involved in overt speech only); (2) the pars orbitalis (with distinct sub-regions responding to phonological and semantic processing); (3) the anterior cingulate and SMA (whose subregions show differential sensitivity to speech and finger press responses); and (4) the cerebellum (with distinct regions for semantic processing, speech production and domain general processing). We also dissociated four different types of phonological effects in, respectively, the left superior temporal sulcus, left putamen, left ventral premoto